Muslims Consumers Attitudes Towards Islamic Finance Products In A Non-Muslim Country (Jurnal Kemanusiaan, 2017)
ABSTRACTThe focal point of Islamic banking is adhering to the shariah law, which prohibits the utilisation of Riba (interest). This banking approach has recently grown in popularity not only in Islamic countries, but has also embryonic in non-Muslim countries. Although these methods is not totally new or revolutionary as it has been written and practiced during the renaissance of the Islamic civilisation, it has yet to establish itself and be tested in the modem world as compared to the conventional banking.Muslims worldwide are still engaged in the "non-interest-free" system in financing their purchases especially those who are staying in the non-Muslim countries. There are many reasons why Muslims still engage in "non-interest-free" products. One of the reasons is the availability of Islamic financial product or non-interest bearing financial instruments offers by the banks. It is quite difficult to find such instruments, as most of them are not easy to get. To some extent, there are only few financial institutions which offer such products. This article attempts to examine the attitude of Muslims staying outside the Islamic world, particularly in the U.K., towards Islamic finance products and will explain whether there is demand for such products from them.It is found out that Muslims living in the U.K. are very much willing to change their practices from indulging in the conventional system into the new system - the Islamic financial system Muslim Consumer Attitude towards Islamic Finance Products in a Non Muslim Country